Immunosenescence markers in T- and NK-cells according to the CD4/CD8 ratio in successfully treated people living with HIV - Vassallo, Matteo; Durant, Jacques; Addou, Sami; Ticchioni, Michel; Fabre, Roxane; Chirio, David; Naqvi, Alissa; Cua, Eric; Ameil, Leslie; Godemert, Maeva; Pradier, Christian; Carles, Michel (Frontiers in Medicine, 2025)
IntroductionThe CD4/CD8 ratio has emerged as a useful indicator of immune dysfunction and comorbid conditions in people living with HIV (PLWH). However, its optimal cut-off value is unclear. We explored the correlation between the CD4/CD8 ratio, immunosenescence markers and comorbid conditions.MethodsWe prospectively included PLWH on successful and stable ART (antiretroviral therapy) > 60 years old and receiving either BIC/FTC/TAF or DTG/3TC, in Nice, France. HIV-negative healthy subjects were included as controls. We measured T-cell subsets (naïve, central memory, effector memory and terminally differentiated cells) and the distribution of KLRG1 + CD57+ senescent cells. We correlated CD4/CD8 ratio, background measurements and comorbid conditions.ResultsWe included 68 PLWH (median age 69 years, 31 years on ART, median CD4/CD8 ratio 0.76). PLWH had higher levels of senescence markers than controls (n = 8). Among PLWH, adjusting for age, gender, HIV follow-up and duration on ART, those with a CD4/CD8 ratio < 0.76 had more senescent CD8+ cells (AdjOR = 0.93, 95%CI = [0.88; 0.97], p-value = 0.003). Higher levels of CD8+ senescence persisted for lower CD4/CD8 ratios, with, in addition, a significant decrease in NK cells in case of a ratio < 0.4. After adjustment, CD8+ effector memory senescent cells were significantly more abundant in PLWH with hypertension.ConclusionPLWH on successful ART display elevated immunosenescence markers, mainly on CD8+ T-cells. A CD4/CD8 cut-off value below 0.4 showed the strongest association with immune dysfunction, including NK+ cells. Such results could be useful for identifying patients requiring closer follow-up and screening for complications.